Ewing’s Sarcoma Disguised as Aneurysmal Bone Cyst Lesion: About a Case - Amine El Khassoui; Mariem Touraif; Driss Tahiri; El Mouhtadi Aghoutane; Tarik Salama; Redouane El Fezzazi (Case Reports in Oncological Medicine)
Aneurysmal bone cysts are defined as benign lesions. They expose the patients to a higher risk of pathological fractures. The typical clinical and radiological aspects of the tumor usually do not require a pathological confirmation before a definite treatment. However, in some cases, a malignant tumor will have the same clinical and radiological characteristics of a begin lesion. Our case highlights this fact. We present a case of a 13-year-old patient that presented to us with a pathological fracture. The X-ray and CT scan were in favor of ABC; however, the postoperative pathology revealed an Ewing sarcoma. A salvage treatment became mandatory after this finding but was refused by the parents, resulting in the death of the patient 6 months later. A biopsy must be mandatory each time we have a suspicious aneurysmal bone cyst even with typical clinical and radiological characteristics before starting a treatment plan.